Livestock-associated Methicillin-resistant Staphylococcus aureus as a New Impendence for Public Health - A. N. Vaganova; S. V. Borisenko; A. M. Sokurova; V. N. Verbov (Журнал инфектологии)
MRSA is the polyphyletic group into Staphylococcus aureus species. In accordance to the hostal preference, this group is divided, to three subgroups, i.e hospital-associated. MRSA, HA-MRSA, which, includes nosocomial staphylococci variants, community-associated MRSA, CA-MRSA, that is related to human environment and livestock-associated MRSA, LA-MRSA, that has zoonotic origin and commonly is associated with livestock. LA-MRSA is widespread in most countries. The serious problem, is the spread, of LA-MRSA carriage in humans that work in closely contact with livestock. Interaction between populations of CA-MRSA and LA-MRSA leads to acquisition, of human pathogenicity-associated, genes in zoonotic MRSA. The variants of LA-MRSA, that can spread between human arises as the result of this process. These staphylococci may be the cause of human diseases, including hospital-acquired, infections. Intensification of animal husbandry determined massive and uncontrollable antibiotic usage and resulted to development and ubiquitous spread of LA-MRSA, that is, in contrast to CA-MRSA, is characterized, by multiple drug resistance. This circumstance make practically impossible to eliminate LA-MRSA in human and livestock environment. In such considerations, monitoring of ecologic, epizootic and epidemiologic situation in human and. livestock becomes one of the main ways to control the spread of MRSA and diseases, associated with it.